An Imine‐Based Molecular Cage with Distinct Binding Sites for Small and Large Alkali Metal Cations. Issue 20 (19th March 2013) - Schouwey, Clément; Scopelliti, Rosario; Severin, Kay
Abstract The synthesis of a cylindrical, imine‐based cage composed of two trimeric metallamacrocycles is described. The cage acts as a heterotopic receptor for alkali metal cations. The small cations Li+, Na+, and K+ bind to the outside of the cage with good selectivity for Li+, whereas the larger cations Rb+ and Cs+ are bound inside the cage to form unusual π complexes with a good selectivity for Cs+. Negative heterotopic cooperativity between the two binding sites is observed. The complexation of Cs+ is associated with a color change, which enables the cage to be used as a specific sensor for Cs+.